2020
DOI: 10.1007/s00392-020-01626-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact of cardiovascular metabolic diseases on COVID-19 in China

Abstract: Background Studies have reminded that cardiovascular metabolic comorbidities made patients more susceptible to suffer 2019 novel corona virus (2019-nCoV) disease , and exacerbated the infection. The aim of this analysis is to determine the association of cardiovascular metabolic diseases with the development of COVID-19. Methods A meta-analysis of eligible studies that summarized the prevalence of cardiovascular metabolic diseases in COVID-19 and compared the incidences of the comorbidities in ICU/severe and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

63
1,750
10
161

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,862 publications
(2,065 citation statements)
references
References 25 publications
63
1,750
10
161
Order By: Relevance
“…A number of studies in the available literature suggest an association between preexisting CVD and severe COVID-19, which are summarized in Tables 1 and 2. A meta-analysis of six studies inclusive of 1,527 patients with COVID-19 examined the prevalence of CVD and reported the prevalence of hypertension, cardiac and cerebrovascular disease, and diabetes to be 17.1%, 16.4%, and 9.7%, respectively (4). Patients who required intensive care unit (ICU) admission were more likely to have these comorbidities compared to non-ICU patients.…”
Section: Prevalence Of Cvd In Patients With Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies in the available literature suggest an association between preexisting CVD and severe COVID-19, which are summarized in Tables 1 and 2. A meta-analysis of six studies inclusive of 1,527 patients with COVID-19 examined the prevalence of CVD and reported the prevalence of hypertension, cardiac and cerebrovascular disease, and diabetes to be 17.1%, 16.4%, and 9.7%, respectively (4). Patients who required intensive care unit (ICU) admission were more likely to have these comorbidities compared to non-ICU patients.…”
Section: Prevalence Of Cvd In Patients With Covid-19mentioning
confidence: 99%
“…Preexisting cardiovascular disease (CVD) may predispose to COVID-19 infection. Those with CVD who are infected by the virus have an elevated risk of adverse outcomes; and infection, itself, is associated with cardiovascular complications (4)(5)(6). Moreover, COVID-19 infection may also have numerous indirect effects relevant to CV health.…”
Section: Introductionmentioning
confidence: 99%
“…ACE2 plays an important role in neurohumoral regulation of CV system in normal health as well as in various disease conditions. The binding of SARS-CoV-2 to ACE2 can result in alteration of ACE2 signaling pathways, leading to acute myocardial and lung injury [3,4]. 2.…”
Section: Pathogenic Considerationsmentioning
confidence: 99%
“…The patients with pre-existing CVD appear to have heightened vulnerability to develop COVID-19 and tend to have more severe disease with worse clinical outcomes [1,4,6,8]. Various CV risk factors also adversely affect porgnosis of these patients, although they do not seem to increase likleihood of developing the infection.…”
Section: Role Of Underling CV Comorbiditiesmentioning
confidence: 99%
“…The spread of the novel SARS-CoV-2 coronavirus (COVID-19) has reached pandemic proportions and represents a threat for increased morbidity and mortality, globally. In many regions this increased morbidity and mortality is particularly seen in older persons and those presenting with co-morbidities such as overt diabetes, obesity and hypertension [1][2][3][4] . The high incidence of diabetes throughout the world makes this particularly concerning as the COVID-19 pandemic progresses.…”
Section: Increased Incidence Of Covid-19 In Patients With Diabetesmentioning
confidence: 99%